1993
DOI: 10.1007/bf02536237
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil inhibits human breast carcinoma growth: A function of increased lipid peroxidation

Abstract: Female athymic nude mice were implanted subcutaneously with human breast carcinoma MDA-MB231. Seven to ten days later, the mice were divided into groups and fed a purified diet containing the following types of fat (% of diet): (i) 20% corn oil (CO); (ii) 15% CO:5% fish (menhaden) oil (FO); (iii) 10% CO:10% FO; (iv) 5% CO:15% FO; (v) 1% CO:19% FO; and (vi) 1% CO:19% FO plus antioxidants (alpha-tocopherol acetate, 2000 IU/kg diet and tertiary butyl-hydroquinone, 2% of total fat). The linoleic acid levels (% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
3
6

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(90 citation statements)
references
References 24 publications
6
75
3
6
Order By: Relevance
“…Our results confirm those of earlier reports (Gonzalez et al, 1991(Gonzalez et al, , 1993) that supplementation of the high fish oil diet with a prooxidant, ferric citrate, suppresses breast cancer growth and increases lipid peroxidation products in human breast cancer growing in nude mice. Our original findings are as follows.…”
Section: Comparisons With Similar Past Researchsupporting
confidence: 92%
“…Our results confirm those of earlier reports (Gonzalez et al, 1991(Gonzalez et al, , 1993) that supplementation of the high fish oil diet with a prooxidant, ferric citrate, suppresses breast cancer growth and increases lipid peroxidation products in human breast cancer growing in nude mice. Our original findings are as follows.…”
Section: Comparisons With Similar Past Researchsupporting
confidence: 92%
“…The increase in DNA synthesis rate was observed at high plasma concentrations of n-6 PUFAs (200-600 gM). In vivo studies have shown that PUFAs of the n-6 class may enhance both chemically induced and transplanted tumour development and that PUFAs of the n-3 class frequently exert (Gonzalez et al, 1993;Noguchi et al, 1995). Our short-term studies on growth-regulatory control by PUFAs does not account for long-term in vivo effects, and a clear correlation between in vivo and in vitro data can therefore not be expected.…”
Section: Discussionmentioning
confidence: 75%
“…13,14). Studies in cell culture and animal models have shown that DHA and eicosapentaenoic acid (20:5, n-3) inhibit tumorigenesis (15,16) and the growth of rodent tumors (17,18) and human breast cancer xenografts (19,20). Importantly, n-3 polyunsaturated fatty acids selectively inhibit tumor cell proliferation and are significantly less toxic towards normal cells (21,22).…”
Section: Introductionmentioning
confidence: 99%